Semi-empirical modelling of the mass flow in a pilot-scale tubular reactor and tracking control. (September 2018) - Caballero-Barragán, H.; Osuna-Ibarra, L.; Sanchez, A.; Loukianov, A.G.
Highlights: A model for a pilot-scale tubular reactor is developed. The resulting model is a linear-varying system with time-varying delay. This model is simulated and compared to the results obtained from the experiments. The tracking control was designed. The robust tracking control is designed for time-invariant and time-variant system. Abstract: In this paper a model for a pilot-scale tubular reactor is developed using aggregated-parameters. The resulting model is a linear-varying system with time-varying delay. This model is simulated and compared to the results obtained from the experiments performed on the pilot-scale tubular reactor. In order to design a tracking control and considering the characteristics of the resulting model, predictive control techniques are used. The predictor is applied and a delay-free system is obtained. A tracking controller using the block control technique is proposed and is applied during simulation, the results are shown.